High-thermal-conductivity and high-uniform-temperature micro-channel structure and processing method thereof

By using diamond/copper composite materials and shrinkable microchannel structures, combined with magnetron sputtering PTFE layer, the existing microchannel structure has solved the thermal resistance of the thermal conductivity side, uneven temperature and flow resistance in high-power chip heat dissipation. The problem of high is to achieve a microchannel structure with high thermal conductivity, high temperature uniformity and low flow resistance, improving the overall heat exchange performance.

CN119495653APending Publication Date: 2025-02-21ZHENGZHOU RES INST FOR ABRASIVES & GRINDING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411745631.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing microchannel structures have problems such as large thermal resistance, uneven temperature and high flow resistance in the heat dissipation of high-power chips, which are difficult to meet the future high-efficiency heat dissipation needs of chips.

Method used

Diamond/copper composite material is used as the main material of the microchannel heat sink, and a shrinkable microchannel structure and acrylic cover plate are installed on it. The height of the shrinking runner decreases from the inlet end to the outlet end, combined with magnetron sputtering Vinyl fluoride layer to reduce flow resistance.

Benefits of technology

It significantly reduces the temperature during the chip operation, increases the outlet side flow rate, enhances the heat exchange effect, reduces the temperature difference between the inlet and outlet, improves the temperature uniformity of the bottom plate, and reduces the flow resistance and improves the overall heat exchange performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495653A_ABST
    Figure CN119495653A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity and high-uniform-temperature microchannel structure and a processing method thereof.A microchannel heat sink and an acrylic cover plate above the microchannel heat sink are arranged, a contraction flow channel is embedded in the acrylic cover plate, the height of the contraction flow channel is gradually decreased from the inlet end to the outlet end, and the main body material of the microchannel heat sink is a diamond / copper composite material; due to high thermal conductivity, the diamond / copper-based micro-channel can greatly reduce the temperature of the chip in the working process, and the contraction type micro-channel can improve the flow velocity of the outlet side, enhance the heat exchange effect, reduce the temperature difference between the inlet and the outlet and enhance the temperature uniformity. The magnetron sputtering polytetrafluoroethylene can make the acrylic flow channel hydrophobic and reduce the flow resistance, so that the design of the micro-channel integrates high heat dissipation, high temperature uniformity and low flow resistance, and the overall heat exchange performance of the existing micro-channel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of microchannel technology, and particularly relates to a high thermal conductivity and high temperature uniformity microchannel structure and a processing method thereof. Background Art

[0002] As semiconductor manufacturing technology and future chip performance requirements increase, future chips will become larger and more powerful, and the heat flux density will also increase rapidly, exceeding 1000 W / cm 2 , which has brought serious pressure to the heat dissipation of the equipment. At the same time, high-power chips have a wide range of applications, involving aerospace, supercomputing centers, data centers, national defense and military industries. Therefore, efficient heat dissipation of chips is very important. Microchannel structure heat dissipation has received more and more attention in recent years because of its large heat transfer specific surface area, high heat transfer efficiency, and compact structure. At present, most microchannels are made of traditional metals and non-metallic materials, such as copper, aluminum, silicon, or glass. Because their thermal conductivity has a natural upper limit and the thermal expansion rate is difficult to adapt to many scenarios, it is difficult to meet current and even future needs. In view of the continuous decline in the cost of artificial diamonds and years of research on diamond / copper composite materials, it is now worth commercial application.

[0003] Diamond / copper composite materials have three outstanding advantages as heat sinks: (1) Diamond / copper composites have extremely high thermal conductivity, which can reach over 900 W / m·K, more than twice that of metallic copper; (2) Diamond / copper composite materials are made of two materials, and their thermal expansion coefficient can be adjusted according to the volume fraction of diamond, making them have a wider range of applications; (3) The thermal conductivity of pure diamond exceeds 2000 W / m·K, but the manufacturing cost of large-scale diamond is high. Compared with diamond substrates, diamond / copper composite substrates have better price advantages.

[0004] Selecting diamond / copper composite materials to process microchannel heat sinks can greatly reduce the thermal resistance on the heat conduction side and improve the heat exchange efficiency. At the same time, the temperature uniformity during the heat dissipation process is also a key point that needs attention. Uneven temperature will lead to the formation of local hot spots, thermal stress and stress fatigue, which will affect the working life and reliability of the chip. The formation of local hot spots will also reduce the service range of the chip. The rise in fluid temperature on the outlet side of the microchannel heat sink will reduce the heat exchange efficiency on the outlet side, thereby causing the outlet side temperature to be high. Reducing the temperature difference between the inlet and outlet of the microchannel also requires continuous optimization.

[0005] The invention of announcement number CN118712153A discloses a uniform temperature microchannel device and a preparation method thereof, wherein the uniform temperature microchannel device comprises: a main body, the material of the main body is a composite material, a plurality of microchannels are provided in the main body, and the microchannels are used for the circulation of liquid working medium; the composite material is composed of a metal matrix and a reinforcement, the reinforcement is arranged in the metal matrix, and the volume fraction of the reinforcement in the composite material changes gradiently along the extension direction of the microchannel, so that the thermal conductivity of the microchannel increases gradiently along the flow direction of the liquid working medium, and the thermal conductivity of the microchannel is continuously increased mainly through a segmented design, and the heat transfer efficiency in the whole heat dissipation process tends to be consistent, thereby improving the uniform temperature and the heat conduction effect, however, the improvement of the uniform temperature of the bottom plate is achieved by arranging composite materials of different thermal conductivities in different regions, and there is a significant effect between different regions, but no optimization is made in the same region; and the flow resistance of the flow channel is not optimized, and still needs to be improved. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies of the above-mentioned prior art and provide a high thermal conductivity and high temperature uniformity microchannel structure and a processing method thereof, which adopts a contraction type microchannel structure to improve the heat dissipation capacity of the existing microchannel heat sink, while reducing the inlet and outlet temperature difference and flow resistance, thereby improving the overall heat exchange performance of the heat sink.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: A high thermal conductivity and high uniform temperature microchannel structure, comprising a microchannel heat sink and an acrylic cover plate above the microchannel heat sink, wherein the acrylic cover plate is embedded with a contraction flow channel; The main body of the microchannel heat sink is made of diamond / copper composite material, and multiple microchannels are opened on the main body. The height of the microchannel is consistent from the inlet end to the outlet end. There are a plurality of contraction channels on the acrylic cover plate, and the height of the contraction channels decreases from the inlet end to the outlet end.

[0008] A polytetrafluoroethylene layer is formed on the surface of the contraction flow channel by magnetron sputtering.

[0009] The main material of the microchannel heat sink is a diamond / copper composite material.

[0010] The contraction flow channel is arranged in a triangular groove.

[0011] A method for processing a high thermal conductivity and high temperature uniformity microchannel structure, comprising the following steps: (1) Determination of microchannel heat sink size Determine the size of the microchannel heat sink based on the requirements, as well as the microchannel flow channel width, the adjacent microchannel rib width and the microchannel height h; (2) Determination of optimal rib height Use ANSYS FLUENT to simulate the microchannel in step (1), determine the maximum temperature simulation results corresponding to different rib heights, and find the optimal microchannel rib height h; (3) Microchannel heat sink heat dissipation effect test Using ANSYS FLUENT, we simulated copper-based microchannels of the same size, and compared the heat dissipation capabilities of diamond / copper-based microchannel heat sinks and pure copper-based microchannel heat sinks to verify whether diamond-copper microchannel heat sinks have heat dissipation advantages. (4) Micro-scale processing of diamond / copper-based microchannel heat sinks Use a picosecond laser to etch microchannels on the diamond / copper-based microchannel heat sink, and attach a high-temperature thermocouple on the back to ensure that the temperature is below 700°C; (5) Acrylic cover processing and surface treatment After the micro grooves are milled by the precision engraving machine, the contraction flow channel is polished with sandpaper and polished to less than 0.05μm. Finally, the contraction flow channel is polished again with fine polishing paste; (6) Cleaning the acrylic cover The acrylic cover plate with the built-in shrinkage channel obtained in step (5) is ultrasonically cleaned using acetone, ethanol, and deionized water successively, and then placed in a vacuum oven for heat drying after cleaning; (7) Magnetron sputtering of polytetrafluoroethylene in acrylic flow channel The acrylic cover plate obtained in step (6) is placed on a magnetron sputtering tray with the flow channel facing upward, and the vacuum is evacuated to below 8×10-4Pa. Polytetrafluoroethylene is magnetron sputtered on the flow channel using a magnetron sputtering apparatus to improve the hydrophobicity of the flow channel surface; (8) Bonding of acrylic cover and microchannel heat sink Apply UV glue to the upper end surface of the ribs of the acrylic cover plate obtained in step (7), and bond it to the diamond / copper-based microchannel heat sink, and use ultraviolet light to cure it to obtain a shrinkable microchannel structure.

[0012] The simulation parameters in step (2) are set as follows: The cooling medium is liquid water, the inlet temperature is set to 300 K, the bottom is a 14 mm × 35 mm rectangular uniform heat source, its centroid coincides with the centroid of the heat sink bottom plate, the heat flux is 1000000 W / m2, the flow state is laminar, and the steady state setting is adopted.

[0013] In step (5), the rib width of the contraction flow channel is set to be the same as the rib width of the microchannel, and the flow channel width of the contraction flow channel is set to be the same as the flow channel width of the microchannel.

[0014] The microchannel flow channel width is set equal to the microchannel rib width.

[0015] The beneficial effects of the present invention are: (1) The present invention discloses a high thermal conductivity and high uniform temperature microchannel structure and a processing method thereof. A microchannel heat sink and an acrylic cover plate above the microchannel heat sink are provided, and a contraction flow channel is embedded in the acrylic cover plate. The height of the contraction flow channel decreases from the inlet end to the outlet end. The main material of the microchannel heat sink is a diamond / copper composite material. Due to its high thermal conductivity, the use of a diamond / copper-based microchannel can significantly reduce the temperature of the chip during operation. The contraction microchannel can increase the outlet flow rate, enhance the heat exchange effect, reduce the inlet and outlet temperature difference, and enhance the uniform temperature. Although the contraction microchannel increases the fluid flow resistance, magnetron sputtering of polytetrafluoroethylene can make the acrylic flow channel hydrophobic and reduce the flow resistance. Therefore, this type of microchannel design integrates high heat dissipation, high uniform temperature, and low flow resistance, thereby improving the overall heat exchange performance of the existing microchannel.

[0016] (2) The present invention utilizes the high thermal conductivity of the diamond / copper composite material to improve the heat transfer efficiency and reduce the bottom plate temperature. At the same time, a contraction flow channel is set to increase the outlet flow rate to improve the heat transfer efficiency in view of the characteristics of low inlet temperature and high outlet temperature of the microchannel, thereby reducing the inlet and outlet temperature difference and improving the temperature uniformity of the bottom plate. In addition, polytetrafluoroethylene is plated inside the flow channel to improve its surface hydrophobicity, thereby reducing the flow resistance of the working fluid, and finally realizing the design of a microchannel structure with high thermal conductivity, high temperature uniformity and low flow resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the structure of the present invention; Figure 2 is a schematic diagram of the structure of a microchannel heat sink; Figure 3 It is a three-dimensional acrylic cover Figure 1 ; Figure 4 It is a three-dimensional acrylic cover Figure 2 ; Figure 5 is a schematic diagram of the maximum temperature of the heat sink bottom plate with different rib heights; Figure 6 It is a schematic diagram of the maximum base plate temperature of two heat sinks under different heat flux densities. DETAILED DESCRIPTION

[0018] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0019] The present invention provides a high thermal conductivity and high temperature uniformity microchannel structure and a processing method thereof, such as Figures 1 to 6 shown.

[0020] A high thermal conductivity and high uniform temperature microchannel structure comprises a microchannel heat sink 2 and an acrylic cover plate 1 connected to the top of the microchannel heat sink 2, wherein the acrylic cover plate 1 is embedded with a contraction flow channel; the main body of the microchannel heat sink 2 is made of a diamond / copper composite material, and a plurality of microchannels are opened on the main body, and the height of the microchannels is consistent from the inlet end to the outlet end; and a plurality of contraction flow channels 13 are spaced apart on the acrylic cover plate 1, and the height of the contraction flow channels 13 decreases from the inlet end to the outlet end.

[0021] The surface of the contraction channel 13 is provided with a polytetrafluoroethylene layer by magnetron sputtering.

[0022] The main material of the microchannel heat sink 2 is a diamond / copper composite material.

[0023] A method for processing a high thermal conductivity and high temperature uniformity microchannel structure, comprising the following steps: (1) Determination of microchannel heat sink size Determine the size of the microchannel heat sink based on the requirements, as well as the width of the microchannel flow channel 23, the adjacent microchannel rib width 22 and the microchannel height h; (2) Determination of optimal rib height Use ANSYS FLUENT to simulate the microchannel in step (1), determine the maximum temperature simulation results corresponding to different rib heights, and find the optimal microchannel rib height h; (3) Microchannel heat sink heat dissipation effect test Using ANSYS FLUENT, we simulated copper-based microchannels of the same size, and compared the heat dissipation capabilities of diamond / copper-based microchannel heat sinks and pure copper-based microchannel heat sinks to verify whether diamond-copper microchannel heat sinks have heat dissipation advantages. (4) Micro-scale processing of diamond / copper-based microchannel heat sinks Use a picosecond laser to etch microchannels on the diamond / copper-based microchannel heat sink, and attach a high-temperature thermocouple on the back to ensure that the temperature is below 700°C; (5) Acrylic cover processing and surface treatment After the micro grooves are milled by the fine engraving machine, the contraction flow channel 13 is polished and polished with sandpaper, and the contraction flow channel 13 is polished to less than 0.05 μm, and finally the contraction flow channel 13 is polished again with a fine polishing paste; (6) Cleaning the acrylic cover The acrylic cover plate with the built-in shrinkage channel obtained in step (5) is ultrasonically cleaned using acetone, ethanol, and deionized water successively, and then placed in a vacuum oven for heat drying after cleaning; (7) Magnetron sputtering of polytetrafluoroethylene in acrylic flow channel Place the acrylic cover plate 1 obtained in step (6) on the magnetron sputtering tray with the flow channel facing upward and evacuate to 8×10 -4 Pa, magnetron sputtering polytetrafluoroethylene is used on the flow channel to improve the hydrophobicity of the flow channel surface; (8) Bonding of acrylic cover and microchannel heat sink UV glue is applied to the upper end surface of the rib 12 of the acrylic cover plate obtained in step (7), and bonded to the diamond / copper-based microchannel heat sink, and cured by ultraviolet light to obtain a shrinkable microchannel structure.

[0024] The simulation parameters in step (2) are set as follows: The cooling medium is liquid water, the inlet temperature is set to 300 K, the bottom is a 14 mm × 35 mm rectangular uniform heat source, its centroid coincides with the centroid of the heat sink bottom plate, and the heat flux is 1000000 W / m 2 , the flow state is laminar, steady state setting.

[0025] In step (5), the rib width of the contraction flow channel is set to be the same as the rib width of the microchannel, and the flow channel width of the contraction flow channel is set to be the same as the flow channel width of the microchannel. Preferably, the flow channel width of the microchannel is set to be the same as the rib width of the microchannel.

[0026] The following is described in conjunction with specific embodiments: The present invention mainly enhances the heat transfer capacity of the traditional microchannel heat sink, and reduces the thermal conductivity and thermal resistance in the heat transfer process by using a high thermal conductivity diamond / copper composite material. Due to the high hardness and high wear resistance of diamond, it cannot be milled by traditional machining, so a picosecond laser is selected to process the composite material. The picosecond pulse width of the laser can control the temperature rise during the processing process to be lower than 700°C. This is because diamond will undergo graphitization in a high-temperature oxygen environment, which in turn affects the heat transfer performance of the composite material. One of the reasons for the enhanced heat transfer of the microchannel is that the ribs between the channels increase the heat transfer area, so the rib height is crucial. If the rib height is not enough, it will be difficult to fully exert the material advantages. If the rib height is too high, there will be no obvious gain in enhanced heat transfer, and the manufacturing cost will increase instead. Therefore, it is very necessary to determine the optimal rib height. At the same time, the rib efficiency is affected by the physical properties of the material, so the present invention numerically simulates the microchannels with different rib heights from low to high, and compares the maximum outlet temperature. When the outlet temperature decreases and has stabilized, it is the optimal rib height.

[0027] A high thermal conductivity and high temperature uniformity microchannel structure design and processing, the specific steps are as follows: (1) Determination of microchannel heat sink size The actual size of the microchannel heat sink can be determined based on actual needs. In the present invention, the size of the microchannel heat sink is 18.5 mm×35 mm, wherein the microchannel processing area is 15.5 mm×35 mm, the microchannel flow channel width is 500 μm, the adjacent microchannel rib width is 500 μm, the heat sink bottom plate 21 thickness is 1 mm, and the microchannel height is h. Figure 1 .

[0028] (2) Determination of optimal rib height Use ANSYS FLUENT 2022R1 to determine the optimal rib height. The simulation is a steady-state calculation. The energy equation is turned on. The flow is laminar. The heat source size is 14 mm × 35 mm. The uniform heat source and the heat flux are 1,000,000 W / m 2 The thermal conductivity of the diamond / copper composite material is set to 900 W / m•K and the density is 6240 kg / m 3 (diamond volume fraction 50%), specific heat capacity 423 J / (kg•K), cooling medium is liquid water, inlet temperature is set to 300 K, flow rate 2 m / s. The rib height h is 1 mm, 3 mm, 5 mm, 7 mm, 9 mm respectively, and the outlet temperature is the highest temperature of the horizontal middle plane of the heat sink bottom plate 21, located on the outlet side. The simulation results of the highest temperature with different rib heights are shown in Figure 4 As shown in the figure, when the rib height exceeds 5 mm, the temperature drops relatively slowly, so 5 mm is selected as the optimal rib height.

[0029] (3) Testing the heat dissipation effect of diamond / copper matrix composite microchannel heat sink Since the thermal conductivity of copper is much lower than that of diamond / copper composite materials, its optimal rib height is lower than that of diamond / copper composite heat sinks. Therefore, 5 mm rib height is selected for both heat sinks. The simulation parameters are kept consistent. The thermal conductivity of the two heat sinks is compared at 1,000,000, 2,000,000, and 3,000,000 W / m 2 The highest temperature under heat flux density, other simulation parameters are consistent with (2), the simulation results are as follows Figure 5 It can be obtained that in high heat flux density scenarios, the diamond / copper composite heat sink can significantly reduce the base plate temperature, and the diamond / copper composite heat sink has significant advantages over traditional heat sinks in high heat flux density scenarios; and it can be expected that by increasing the flow rate of the liquid working fluid, the diamond / copper heat sink will expand the heat dissipation advantage in high heat flux density scenarios.

[0030] (4) Micro-scale processing of diamond / copper composite materials The microchannels were etched using a picosecond laser at a frequency of 2500 Khz, a power of 100 W, and a wavelength of 1100 nm, and a high-temperature thermocouple was attached to the back to ensure that its temperature was below 700 °C.

[0031] (5) Micro-groove acrylic sheet processing and surface treatment After the micro-grooves are milled with a precision engraving machine, the flow channel is first polished with 400# sandpaper, and then the acrylic flow channel is polished to less than 0.05 μm with 800#, 2000#, and 4000# sandpaper, and finally the flow channel is polished with a fine polishing paste.

[0032] (6) The acrylic cover plate 1 with the embedded flow channel obtained in (5) was ultrasonically cleaned using acetone, ethanol, and deionized water in sequence. The ultrasonic temperature was set to 35 °C and the ultrasonic cleaning was performed for 10 min each time. Finally, the acrylic cover plate 1 was placed in a vacuum oven with the oven temperature set to 60 °C and heated for 20 min.

[0033] (7) Place the acrylic cover plate 1 obtained in (6) on the magnetron sputtering tray with the flow channel facing upward and evacuate to 8×10 - 4 Below Pa, the argon flow rate was set to 50 sccm, the RF sputtering power was 200 W, the bias voltage was set to 50 V, and the sputtering was performed for 20 min.

[0034] (8) Apply UV glue to the upper end surface of the acrylic cover rib 12 obtained in (7), and bond it to the diamond / copper heat sink. Use ultraviolet light or the like to cure it for 3 minutes to obtain the shrinkage microchannel structure. The structure after bonding is as shown in FIG. Figure 1 shown.

[0035] The present invention improves the temperature uniformity of the microchannel, increases the outlet flow rate by designing a contraction-type microchannel, and achieves the effect of reducing the outlet temperature. If the diamond / copper composite material is directly processed into a trapezoidal microchannel, it is necessary to increase the specifications and processing dimensions of the diamond / copper composite material, which greatly increases the cost and has no obvious heat exchange enhancement effect. This is because the high thermal conductivity of diamond / copper contributes greatly to the flow heat exchange when the rib height is within the optimal rib height, but the heat exchange contribution is relatively small when it exceeds this size. At the same time, since the contraction-type channel brings flow resistance, the flow resistance should be reduced. The present invention reduces the flow resistance by magnetron sputtering polytetrafluoroethylene on the surface of the flow channel where the heat exchange is not significant, and increasing the wall wetting angle, but the surface roughness of the diamond / copper composite material is more difficult to control, the magnetron coating process is more complicated, and the drag reduction is more difficult to achieve than the acrylic surface. In summary, it is more advantageous to choose to dig a triangular groove inside the acrylic plate, that is, to contract the flow channel, and then make a hydrophobic coating and bond it to the diamond / copper microchannel heat sink.

[0036] If the words "first", "second" and the like are used in this patent to limit components, those skilled in the art should know that the use of "first" and "second" is only for the convenience of describing the present invention and simplifying the description, and the above words have no special meaning.

[0037] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the invention claimed for protection. The scope of protection claimed for the present invention is defined by the attached claims and their equivalents.

[0038] In the description of the present invention, it is necessary to understand that the terms "front", "rear", "left", "right", "center", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the protection content of the present invention.

Claims

1. A high thermal conductivity and high temperature uniformity microchannel structure, characterized in that: It includes a microchannel heat sink and an acrylic cover plate thereon, wherein a contraction flow channel is embedded in the acrylic cover plate; The main body of the microchannel heat sink is made of diamond / copper composite material, and multiple microchannels are opened on the main body. The height of the microchannel is consistent from the inlet end to the outlet end. There are a plurality of contraction channels on the acrylic cover plate, and the height of the contraction channels decreases from the inlet end to the outlet end.

2. A high thermal conductivity and high uniform temperature microchannel structure according to claim 1, characterized in that: A polytetrafluoroethylene layer is formed on the surface of the contraction flow channel by magnetron sputtering.

3. The high thermal conductivity and high uniform temperature microchannel structure according to claim 1, characterized in that: The main material of the microchannel heat sink is a diamond / copper composite material.

4. The high thermal conductivity and high uniform temperature microchannel structure according to claim 1, characterized in that: The contraction flow channel is arranged in a triangular channel.

5. A method for processing a high thermal conductivity and high temperature uniformity microchannel structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Determination of microchannel heat sink size Determine the size of the microchannel heat sink based on the requirements, as well as the microchannel flow channel width, the adjacent microchannel rib width and the microchannel height h; (2) Determination of optimal rib height Use ANSYS FLUENT to simulate the microchannel in step (1), determine the maximum temperature simulation results corresponding to different rib heights, and find the optimal microchannel rib height h; (3) Microchannel heat sink heat dissipation effect test Using ANSYS FLUENT, we simulated copper-based microchannels of the same size, and compared the heat dissipation capabilities of diamond / copper-based microchannel heat sinks and pure copper-based microchannel heat sinks to verify whether diamond-copper microchannel heat sinks have heat dissipation advantages. (4) Micro-scale processing of diamond / copper-based microchannel heat sinks Use a picosecond laser to etch microchannels on the diamond / copper-based microchannel heat sink, and attach a high-temperature thermocouple on the back to ensure that the temperature is below 700°C; (5) Acrylic cover processing and surface treatment After the micro grooves are milled by the precision engraving machine, the contraction flow channel is polished with sandpaper and polished to less than 0.05μm. Finally, the contraction flow channel is polished again with fine polishing paste; (6) Cleaning the acrylic cover The acrylic cover plate with the built-in shrinkage channel obtained in step (5) is ultrasonically cleaned using acetone, ethanol, and deionized water successively, and then placed in a vacuum oven for heat drying after cleaning; (7) Magnetron sputtering of polytetrafluoroethylene in acrylic flow channel Place the acrylic cover obtained in step (6) on the magnetron sputtering tray with the flow channel facing upward and evacuate to 8×10 -4 Pa, magnetron sputtering polytetrafluoroethylene is used on the flow channel to improve the hydrophobicity of the flow channel surface; (8) Bonding of acrylic cover and microchannel heat sink Apply UV glue to the upper end surface of the ribs of the acrylic cover plate obtained in step (7), and bond it to the diamond / copper-based microchannel heat sink, and use ultraviolet light to cure it to obtain a shrinkable microchannel structure.

6. The method for processing a high thermal conductivity and high temperature uniformity microchannel structure according to claim 5, characterized in that: The simulation parameters in step (2) are set as follows: The cooling medium is liquid water, the inlet temperature is set to 300 K, the bottom is a 14 mm × 35 mm rectangular uniform heat source, its centroid coincides with the centroid of the heat sink bottom plate, and the heat flux is 1000000 W / m 2 , the flow state is laminar, steady state setting.

7. The method for processing a high thermal conductivity and high temperature uniformity microchannel structure according to claim 5, characterized in that: In step (5), the rib width of the contraction flow channel is set to be the same as the rib width of the microchannel, and the flow channel width of the contraction flow channel is set to be the same as the flow channel width of the microchannel.

8. The method for processing a high thermal conductivity and high temperature uniformity microchannel structure according to claim 5, characterized in that: The microchannel flow channel width is set equal to the microchannel rib width.

Citation Information

Cited By

  • Laminated micro-channel heat sink based on composite material rhombic fin array

    CN120711690A